(untitled) - Harry A Carey (Rome, Italy, 1999)
The book was prepared as a teaching and learning guide to be used in the pre-service and in-service education of extension staff, community development workers and all those who work and serve in rural communities.
Keywords: agricultural extension work,agriculture - study and teaching,rural extension